Chronotype is associated with the timing of the circadian clock and sleep in toddlers. (14th March 2014) - Simpkin, Charles T.; Jenni, Oskar G.; Carskadon, Mary A.; Wright, Kenneth P.; Akacem, Lameese D.; Garlo, Katherine G.; LeBourgeois, Monique K.
Summary Chronotype is a construct reflecting individual differences in diurnal preference. Although chronotype has been studied extensively in school‐age children, adolescents and adults, data on young children are scarce. This study describes chronotype and its relationship to the timing of the circadian clock and sleep in 48 healthy children aged 30–36 months (33.4 ± 2.1 months; 24 males). Parents completed the Children's Chronotype Questionnaire (CCTQ) ~2 weeks before the start of the study. The CCTQ provides three measures of chronotype: midsleep time on free days, a multi‐item morningness/eveningness score and a single item chronotype score. After 5 days of sleeping on their habitual schedule (assessed with actigraphy and sleep diaries), children participated in an in‐home salivary dim light melatonin onset assessment. Average midsleep time on free days was 1:47 ± 0:35, and the average morningness/eveningness score was 26.8 ± 4.3. Most toddlers (58.4%) were rated as 'definitely a morning type' or 'rather morning than evening type', while none (0%) were rated as 'definitely evening type'. More morning types (midsleep time on free days and morningness/eveningness score, respectively) had earlier melatonin onset times (r = 0.45, r = 0.26), earlier habitual bedtimes (r = 0.78, r = 0.54), sleep onset times (r = 0.80, r = 0.52), sleep midpoint times (r = 0.90, r = 0.53) and wake times (r = 0.74, r = 0.34). Parent ratings using the single‐item chronotype score were associated with melatonin onset (r = 0.32) and habitual bedtimes (r = 0.27), sleep onset times (r = 0.33) and sleep midpoint times (r = 0.27). Morningness may best characterize circadian preference in early childhood. Associations between chronotype and circadian physiology and sleep timing suggest adequate validity for the CCTQ in this age group. These findings have important implications for understanding the marked variability in sleep timing during the early years of life.